ASAL USUL NAMA PASANGKAYU: Teori Interaksionisme Simbolik - Gazali; Yunidar; Arini Nurazizah; I Made Sukanata (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This study describes the origin of the name Pasangkayu using the symbolic interactionism theory. The data source of this research is the coastal community who master and have knowledge about the origin of the name Pasangkayu by using qualitative descriptive methods. The data collection techniques used in this research are: (1) observation, to make direct observations of the community and the studied object; (2) interviews, to obtain information related to the studied object; (3) audio visual documentation, to record the speaker's explanation related to the origin of the name Pasangkayu; (4) textual documentation, to write all the utterances conveyed and to strengthen the obtained data. The results of the interview provide an overview of how the name Pasangkayu formed to be. The symbolic interactionism carried out by the fishermen was the reason for the naming of Pasangkayu City. The fishermen make a pair of wooden trees as a symbol when returning from the sea.